Absence of M-Ras modulates social behavior in mice. Issue 1 (December 2015) - Ehrhardt, Annette; Wang, Bin; Leung, Marie; Schrader, John
Abstract Background The molecular mechanisms that determine social behavior are poorly understood. Pheromones play a critical role in social recognition in most animals, including mice, but how these are converted into behavioral responses is largely unknown. Here, we report that the absence of the small GTPase M-Ras affects social behavior in mice. Results In their interactions with other males, Mras −/ − males exhibited high levels of territorial aggression and social investigations, and increased fear-related behavior. They also showed increased mating behavior with females. Curiously, increased aggression and mating behaviors were only observed whenMras −/ − males were paired withMras −/ − partners, but were significantly reduced when paired with wild-type (WT) mice. Since mice use pheromonal cues to identify other individuals, we explored the possibility that pheromone detection may be altered inMras −/ − mice. Unlike WT mice, Mras −/ − did not show a preference for exploring unfamiliar urinary pheromones or unfamiliar isogenic mice. Although this could indicate that vomeronasal function and/or olfactory learning may be compromised inMras −/ − mice, these observations were not fully consistent with the differential behavioral responses to WT andMras −/ − interaction partners byMras −/ − males. In addition, induction ofc -fos upon pheromone exposure or in response to mating was similar in WT andMras −/ − mice, as was the ex vivo expansion of neural progenitors with EGF. This indicated that acute pheromone detection and processing was likely intact. However, urinary metabolite profiles differed betweenMras −/ − and WT males. Conclusions The changes in behaviors displayed byMras −/ − mice are likely due to a complex combination of factors that may include an inherent predisposition to increased aggression and sexual behavior, and the production of distinct pheromones that could override the preference for unfamiliar social odors. Olfactory and/or social learning processes may thus be compromised inMras −/ − mice.